Effect of aging on the availability of amino acids from an immune-enhancing diet (IED) after a surgical stress in rats. Issue 9 (September 2020) - Tennoune, N.; Ventura, G.; Le Plenier, S.; Choisy, C.; Neveux, N.; Nakib, S.; Sarfati, G.; Raynaud-Simon, A.; Cynober, L.; De Bandt, J.P.
Summary: Background & aims: Dietary amino acid (AA) requirements increase after a surgical stress while the systemic AA availability from the diet decreases with age, due to splanchnic sequestration. While immune-enhancing diets (IEDs) have been recommended for the nutritional management of surgical patients, the systemic bioavailability of their AA supply has not been evaluated in elderly surgical patients. This was determined in surgically-stressed IED-fed aged rats. Methods: Thirty-four 5-month- or 21-month-old male Sprague–Dawley rats were used. After a gastrostomy and placement of a jugular vein catheter and a one-week recovery period, the animals underwent two 24 h-enteral feedings with an arginine-enriched IED (Impact®, Nestlé Health Science) before (healthy state) and 18 h after a standardized laparotomy, used as a model of surgical stress. During enteral nutrition, blood samples were repeatedly collected to measure plasma AA bioavailability (incremental areas under the curve) at 2, 5 and 24 h. Surgical stress was evaluated from urinary catecholamines and plasma protein profile. Results: Whatever the age or stress situation, IED feeding was associated with decreased plasma glycine and increased alanine, proline and arginine. Aging was mainly associated with a delayed plasma AA accumulation in the first hours after the initiation of enteral nutrition. Stress was associated with higher plasma arginine increase and lower histidine, methionine, phenylalanine and tyrosine accumulation. Age and stress interactions seem limited. Conclusions: AA bioavailability from an arginine-enriched IED seems to be maintained whatever age and stress situation. Aging appears to be mainly associated with a delay in plasma AA accumulation probably related to age-associated splanchnic sequestration of AAs. Additional effects of surgical stress per se seem limited.